THE MASTERY ON ENGLISH IDIOM OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF TEACHER AND EDUCATION FACULTY OF MULAWARMAN UNIVERSITY SAMARINDA IN ACADEMIC YEAR 2004/2005 - Aidar Erika Toding Pali (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2017)
Toding Pali, Aidar  Erika. 2005.The mastery on English Idiom of the fourth semester students of English Department of Teacher and Education Faculty of Mulawarman University Samarinda in Academic Year 2004/2005. The Advisors: (1) Dra. Surya Sili, MAT, Ph.D., (2) Drs. M. Natsir, M.Pd. The purposes of the study are to find out or to know the mastery of English idiom and to find out the score distribution of English Department of Teacher Training and Education Faculty of Mulawarman University Samarinda in Academic Year 2004/2005. The research is descriptive quantitative research.The result of the research show that the total mean score of research is 52.54 with the conclusion of the mastery on English idiom is poor. The quantitative and qualitative analysis of standard score on English idiom show that 0% of the students get excellent scores, 20.83% get good scores, 20.83% get fair scores, 29.16% get poor scores, and 29.16% get fail scores. The percentage of total correct answers of each kind of English idiom are; Idiomatic pairs 52.5%, Similes 38.9%, Phrasal verbs 47.5%, Action which represent feelings 58.3%, Sayings 72.9%, Typical conversational phrase 52.5% and Idiom with preposition 45.8%. The most difficult idiom is Similes and easiest idiom is Sayings.The implication of this research shown that English idiom is an integral parts of vocabulary subject and it is important to be learned. It means that the students need to study and improve their ability in English idiom mastery as it really important in the mastery of English language.